Bovine Neosporosis The major culprit for abortion at dairy farm - Kumar, Niranjan; Samanta, S.; Adeppa, J. (Indian Farming, 2015)
N. caninum is one of the principal causes of bovine abortions in many countries all over the world. During the last decade, a great progress has been be made in the identification of the pathogen and in the knowledge about the biology. So far, all possible definitive and intermediate hosts, the risk factors for the transmission, the pathogenesis of abortions caused and the measures for prevention and control of infection are not fully recognized. It is proved that the vertical transmission is the main route of infection but the elimination of vertical transmission is not sufficient for its eradication in farms as the horizontal transmission of infection is also possible. The control of N. caninum infections includes prevention of both vertical and horizontal transmission, including a serological study for determination of seroprevalence and excluding the seropositive animals from reproduction.